EXAMINING EXTERNAL PRESSURES ON INSTITUTIONAL CAPACITY AND SUSTAINABLE TOURISM DESTINATION IN MYANMAR: A THEMATIC ANALYSIS - Toh, Thet Lwin; Bhaumik, Amiya; Chakkaravarthy, Midhun; Htet, Arkar (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Sustainable tourism in Myanmar faces mounting challenges from political instability, economic volatility, social pressures, and technological limitations. While these PEST factors shape tourism outcomes, limited research has explored how institutional capacity mediates their impact in fragile national contexts. This study examines the interplay between external pressures and institutional responses to understand pathways toward sustainable tourism development in Myanmar. A qualitative research design was employed, drawing on semi-structured interviews with 20 stakeholders across Myanmar’s tourism sector, including policymakers, operators, and community leaders. Data were analyzed using Braun and Clarke’s six-phase thematic analysis to identify patterns related to PEST factors, institutional capacity, and sustainability outcomes. Findings reveal that political and economic instability are the most critical barriers to tourism development, compounded by labor migration, cultural neglect, and weak technological infrastructure. Despite these challenges, institutional capacity expressed through community engagement, workforce training, and adaptive strategies emerged as a key mediator in mitigating external pressures. Discussion/Implications: The study contributes theoretical insights by demonstrating the mediating role of institutional capacity in volatile environments and provides practical recommendations for strengthening governance frameworks, fostering public-private partnerships, and enhancing technological investment. These implications are relevant for policymakers and practitioners seeking to build resilience and advance sustainable tourism not only in Myanmar but also in similarly fragile contexts.